1995
DOI: 10.1063/1.868671
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of liquid surface rheology of surfactant solutions by droplet shape oscillations: Theory

Abstract: The stability of bicontinuous microemulsions: A molecular theory of the bending elastic properties of monolayers comprised of ionic surfactants and nonionic cosurfactants J. Chem. Phys. 103, 4765 (1995); 10.1063/1.470612Twodimensional modeling of the electrorheological behavior of liquid crystalline polymer solutions Surface density of soluble surfactants at the air/water interface: Adsorption equilibrium studied by second harmonic generation J. Chem. Phys. 95, 4620 (1991);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…The resulting surface tension gradient gives rise to a redistribution of surfactant molecules over the droplet interface, which counteracts the droplet deformation. This additional resistance to deformation of the droplet increases the decay rate of the oscillation amplitude (Lu and Apfel 1991;Tian et al 1995). This effect of surfactants is usually called the Gibbs elasticity, and its influence on the oscillation frequency and damping rate has been reported before for oscillating mm-sized droplets of surfactant solutions .…”
Section: Resultsmentioning
confidence: 99%
“…The resulting surface tension gradient gives rise to a redistribution of surfactant molecules over the droplet interface, which counteracts the droplet deformation. This additional resistance to deformation of the droplet increases the decay rate of the oscillation amplitude (Lu and Apfel 1991;Tian et al 1995). This effect of surfactants is usually called the Gibbs elasticity, and its influence on the oscillation frequency and damping rate has been reported before for oscillating mm-sized droplets of surfactant solutions .…”
Section: Resultsmentioning
confidence: 99%
“…The materials were surfactant solutions, and the drops were levitated due to the microgravity conditions of the experiment. In these studies, complementary effects of the bulk and the surface viscosities were found [9] and quantified [10]. Most recently, the oscillating drop method was proposed and developed for measuring polymeric time scales [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the existing literature discusses the measurement of material parameters, such as the dynamic viscosity of the liquid and its surface tension against the ambient medium, predominantly for Newtonian liquids [5][6][7][8]. For viscoelastic systems, the oscillating drop method was used for investigating the surface rheology [9,10]. The materials were surfactant solutions, and the drops were levitated due to the microgravity conditions of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…This approach could be extended to describe elastic modes of surface as well as their nonlinear coupling to capillary waves. The double-periodic structure of the elliptic solutions [11] could describe the new family of normal wave modes predicted in [4].…”
mentioning
confidence: 99%
“…Besides their direct use in rheological and surfactant theory [1][2][3][4][5][6][7], such models apply to cluster physics [8], super-and hyper-deformed nuclei [1], nuclear break-up and fission [2,3,8], thin films [9], radar [4] and even stellar masses and supernova [1,10]. Theoretical approaches are usually based on numerical calculations within different NLD models, [2][3][4] and explain/predict axis-symmetric, non-linear oscillations that are in very good agreement with experiment [1,[5][6][7]. However, there are experimental results which show non-axis-symmetric modes; for example, traveling rotational shapes [5,6] that can lead to fission, cluster emission, or fusion [5][6][7].…”
mentioning
confidence: 99%